2022
DOI: 10.1111/dom.14816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 26 weeks of treatment with empagliflozin versus glimepiride on the myocardial glucose metabolic rate in patients with type 2 diabetes: The randomized, open‐label, crossover, active‐comparator FIORE trial

Abstract: Aim To determine whether treatment with empagliflozin was able to affect the myocardial glucose metabolic rate, as assessed by cardiac dynamic 18F‐fluorodeoxyglucose‐positron emission tomography (18F‐FDG‐PET) combined with euglycaemic‐hyperinsulinaemic clamp compared with glimepiride in patients with type 2 diabetes. Materials and Methods To further investigate the cardioprotective mechanism of sodium‐glucose co‐transporter‐2 inhibitors, we performed a 26‐week, randomized, open‐label, crossover, active‐compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
2
4
0
Order By: Relevance
“…The present findings are in agreement with those of previous studies showing the mechanisms of SGLT2 inhibitors on myocardial glucose metabolism assessed by PET with 18 F-FDG combined with euglycemic-hyperinsulinemic clamp [39][40][41]. A previous study showed that 4-week treatment with dapagliflozin reduced epicardial adipose tissue glucose uptake in patients with T2DM and stable coronary artery disease improving myocardial flow reserve [39].…”
Section: Discussionsupporting
confidence: 93%
“…The present findings are in agreement with those of previous studies showing the mechanisms of SGLT2 inhibitors on myocardial glucose metabolism assessed by PET with 18 F-FDG combined with euglycemic-hyperinsulinemic clamp [39][40][41]. A previous study showed that 4-week treatment with dapagliflozin reduced epicardial adipose tissue glucose uptake in patients with T2DM and stable coronary artery disease improving myocardial flow reserve [39].…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with the study published by Latva-Rasku and colleagues, which demonstrated that 8-week treatment with dapagliflozin does not affect tissue insulin sensitivity and MGU as measured with PET in T2D patients [ 25 ], but contrasts with other studies which instead described an increase in insulin sensitivity [ 26 28 ]. Succurro et al [ 29 ] recently demonstrated that T2D patients randomized to empagliflozin showed a significant reduction in MGU during hyperinsulinemic euglycemic clamp after 26 weeks of treatment as compared to patients randomized to glimepiride who showed an increase in MGU. Empagliflozin treatment was also associated with a significant increase in WBGU compared to glimepiride, which induced a reduction in WBGU.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the present study has several limitations that should be addressed in the near future regarding the interactions of different treatment drugs with insulin-related plaque accumulation. As proposed by previous works [ 37 , 38 , 39 ], antidiabetic and antihypertensive drugs could have interfered with the myocardial glucose metabolism and therefore their relationship with T2D-related CACs should be independently studied. Moreover, antiaggregant therapy could be useful to avoid CACs and presents itself as a very good alternative to avoid the counter-effects of insulin intake [ 40 ].…”
Section: Discussionmentioning
confidence: 99%